Pênfigo vulgar: uma manifestação cutânea autoimune na síndrome pós-Covid-19 - Branco, Rebecca Castelo; Monteiro-Neto, Antônio Urbano; Medeiros, Vanessa Lucilia Silveira de (Avanços em Medicina, 2025)
Comentário